Leprosy type-I reaction episode mimicking facial cellulitis-the importance of early diagnosis - Tania Rita Moreno de Oliveira Fernandes; Graziele Áquila de Souza Brandão; Bruno de Castro e Souza (Sociedade Brasileira de Dermatologia, 2015)
AbstractLeprosy is aneasily recognizable disease due to its dermato-neurological manifestations. It must be present in the physician's diagnostic repertoire, especially for those working in endemic areas. However, leprosy reaction is not always easily recognized by non-dermatologists, becoming one of the major problems in the management of patients with leprosy, as it presents clinical complications characterized by inflammatory process, accompanied by pain, malaise and sometimes the establishment or worsening of the patient's disabilities. We report the case of a patient with type-1 periorbital reaction admitted to the hospital, diagnosed and treated as facial cellulitis, whose late diagnosis may have contributed to the appearance or worsening of facial neuritis.